From broadband to electrochromic notch filters with printed monochiral carbon nanotubes - Berger, Felix J.; Higgins, Thomas M.; Rother, Marcel; Graf, Arko; Zakharko, Yuriy; Matthiesen, Maik; Gotthardt, Jan M.; Zaumseil, Jana (ACS applied materials & interfaces, 2018)
Dense layers of semiconducting single-walled carbon nanotubes (SWNTs) serve as electrochromic (EC) materials in the near-infrared with high optical density and high conductivity. EC cells with tunable notch filter properties instead of broadband absorption are created via highly selective dispersion of specific semiconducting SWNTs through polymer-wrapping followed by deposition of thick films by aerosol-jet printing. A simple planar geometry with spray-coated mixed SWNTs as the counter electrode renders transparent metal oxides redundant and facilitates complete bleaching within a few seconds through iongel electrolytes with high ionic conductivities. Monochiral (6,5) SWNT films as working electrodes exhibit a narrow absorption band at 997 nm (full width at half-maximum of 55–73 nm) with voltage-dependent optical densities between 0.2 and 4.5 and a modulation depth of up to 43 dB. These (6,5) SWNT notch filters can retain more than 95% of maximum bleaching for several hours under open-circuit conditions. In addition, different levels of transmission can be set by applying constant low voltage (1.5 V) pulses with modulated width or by a given number of fixed short pulses.
Gesehen am 17.06.2019